Optimal. Leaf size=19 \[ \frac {3 e^{-x^2}}{-6+e^{x^2}+x} \]
________________________________________________________________________________________
Rubi [F] time = 1.00, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {-3+36 x-12 e^{x^2} x-6 x^2}{e^{3 x^2}+e^{2 x^2} (-12+2 x)+e^{x^2} \left (36-12 x+x^2\right )} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {3 e^{-x^2} \left (-1-4 \left (-3+e^{x^2}\right ) x-2 x^2\right )}{\left (6-e^{x^2}-x\right )^2} \, dx\\ &=3 \int \frac {e^{-x^2} \left (-1-4 \left (-3+e^{x^2}\right ) x-2 x^2\right )}{\left (6-e^{x^2}-x\right )^2} \, dx\\ &=3 \int \left (-\frac {4 e^{-x^2} x}{-6+e^{x^2}+x}+\frac {e^{-x^2} \left (-1-12 x+2 x^2\right )}{\left (-6+e^{x^2}+x\right )^2}\right ) \, dx\\ &=3 \int \frac {e^{-x^2} \left (-1-12 x+2 x^2\right )}{\left (-6+e^{x^2}+x\right )^2} \, dx-12 \int \frac {e^{-x^2} x}{-6+e^{x^2}+x} \, dx\\ &=3 \int \left (-\frac {e^{-x^2}}{\left (-6+e^{x^2}+x\right )^2}-\frac {12 e^{-x^2} x}{\left (-6+e^{x^2}+x\right )^2}+\frac {2 e^{-x^2} x^2}{\left (-6+e^{x^2}+x\right )^2}\right ) \, dx-12 \int \frac {e^{-x^2} x}{-6+e^{x^2}+x} \, dx\\ &=-\left (3 \int \frac {e^{-x^2}}{\left (-6+e^{x^2}+x\right )^2} \, dx\right )+6 \int \frac {e^{-x^2} x^2}{\left (-6+e^{x^2}+x\right )^2} \, dx-12 \int \frac {e^{-x^2} x}{-6+e^{x^2}+x} \, dx-36 \int \frac {e^{-x^2} x}{\left (-6+e^{x^2}+x\right )^2} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.23, size = 19, normalized size = 1.00 \begin {gather*} \frac {3 e^{-x^2}}{-6+e^{x^2}+x} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.82, size = 19, normalized size = 1.00 \begin {gather*} \frac {3}{{\left (x - 6\right )} e^{\left (x^{2}\right )} + e^{\left (2 \, x^{2}\right )}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.22, size = 23, normalized size = 1.21 \begin {gather*} \frac {3}{x e^{\left (x^{2}\right )} + e^{\left (2 \, x^{2}\right )} - 6 \, e^{\left (x^{2}\right )}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.06, size = 18, normalized size = 0.95
method | result | size |
norman | \(\frac {3 \,{\mathrm e}^{-x^{2}}}{{\mathrm e}^{x^{2}}+x -6}\) | \(18\) |
risch | \(\frac {3 \,{\mathrm e}^{-x^{2}}}{x -6}-\frac {3}{\left (x -6\right ) \left ({\mathrm e}^{x^{2}}+x -6\right )}\) | \(31\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [F] time = 0.00, size = 0, normalized size = 0.00 \begin {gather*} -3 \, \int \frac {2 \, x^{2} + 4 \, x e^{\left (x^{2}\right )} - 12 \, x + 1}{2 \, {\left (x - 6\right )} e^{\left (2 \, x^{2}\right )} + {\left (x^{2} - 12 \, x + 36\right )} e^{\left (x^{2}\right )} + e^{\left (3 \, x^{2}\right )}}\,{d x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 0.17, size = 19, normalized size = 1.00 \begin {gather*} \frac {3}{{\mathrm {e}}^{2\,x^2}+{\mathrm {e}}^{x^2}\,\left (x-6\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.15, size = 27, normalized size = 1.42 \begin {gather*} - \frac {3}{x^{2} - 12 x + \left (x - 6\right ) e^{x^{2}} + 36} + \frac {3 e^{- x^{2}}}{x - 6} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________